In vivo dosimetry with an electronic portal imaging device for prostate cancer radiotherapy with an endorectal balloon. (October 2019) - Sterckx, Bo; Steinseifer, Isabell; Wendling, Markus
Abstract: Electronic portal imaging device-based in vivo dosimetry with a commercial product was performed for 10 prostate cancer patients treated with an air-filled endorectal balloon. With the conventional in vivo method the verification results were outside of our clinical acceptance criteria for all patients. The in aqua vivo method, originally developed for lung cancer treatments, proved to be a practical solution to this problem. On average the percentage of points within γ agreement of 3% and 3 mm significantly improved from 90.9% ± 2.5% (1SD) for the conventional in vivo method to 99.0% ± 1.0% (1SD) for the in aqua vivo method.